2012
DOI: 10.5603/nmr-18727
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium radionuclide ventriculography in the assessment of cardiotoxicity of chemotherapy and chemoradiotherapy in patients with breast cancer

Abstract: Radionuclide ventriculography is a useful method of evaluating the cardiotoxicity of the treatment. Early indicators of myocardial damage are EF, PFR, ESvol and EDvol.AC chemotherapy, where the average cumulative dose of anthracyclines was higher, caused more cardiotoxic effects than AT chemotherapy.Applying additional radiotherapy did not significantly increase the cardiotoxicity of the treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Given the easy use of echocardiographic parameters and the sensitivity of serum hs‐cTnT levels, we explored whether the combination of these parameters could help predict the subclinical change of anthracycline‐induced cardiotoxicity. In our present study, we used the nuclear cardiac imaging as a gold standard to estimate the efficacy of these combined indexes . The LVEF and peak filling rate (PFR) which can be extracted from multiple uptake gated acquisition (MUGA) scan are early indicators of LV systolic and diastolic dysfunction…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the easy use of echocardiographic parameters and the sensitivity of serum hs‐cTnT levels, we explored whether the combination of these parameters could help predict the subclinical change of anthracycline‐induced cardiotoxicity. In our present study, we used the nuclear cardiac imaging as a gold standard to estimate the efficacy of these combined indexes . The LVEF and peak filling rate (PFR) which can be extracted from multiple uptake gated acquisition (MUGA) scan are early indicators of LV systolic and diastolic dysfunction…”
Section: Introductionmentioning
confidence: 99%
“…In our present study, we used the nuclear cardiac imaging as a gold standard to estimate the efficacy of these combined indexes. 7 The LVEF and peak filling rate (PFR) which can be extracted from multiple uptake gated acquisition (MUGA) scan are early indicators of LV systolic and diastolic dysfunction. 8…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, radiation therapy and chemotherapy drugs are pericardial irritants and as such increase the risk of pericardial effusion complications, making early diagnosis critical to decrease primary or contributory associated deaths seen in ~86% of symptomatic cancer patients . Radiation‐induced heart disease such as coronary artery disease, valvular disease, constructive pericarditis and myocardial dysfunction including congestive heart failure can significantly limit a patient's quality of life . Thus, it is imperative to effectively ascertain the extent of a patient's risk for a cardiac event.…”
Section: Tc‐99m Multigated Radionuclide Angiographymentioning
confidence: 99%
“…Following radiopharmaceutical administration, planar, SPECT or combination acquisitions are obtained . To visualise all left ventricular wall segments, positioning for planar acquisition includes anterior, lateral, and left anterior oblique (LAO) views with a caudal tilt to best isolate the left ventricle from the left atrium and facilitate accurate processing . Using electrocardiogram leads, images are simultaneously registered with the patient's gated heartbeat to evaluate regional left ventricular wall motion and contractility .…”
Section: Tc‐99m Multigated Radionuclide Angiographymentioning
confidence: 99%
“…Some drugs that are used in together includes Cy-Review clophosphamide (Cytoxan), Doxorubicin (Adriamycin) or Epirubicin (Ellence), 5-fluorouracil (Adrucil), Methotrexate (Rheumatrex), Paclitaxel (Taxol) or Docetaxel (Taxotere), Herceptin and 2-deoxy-D-glucose (2DG) [1,17]. A number of previous studies have shown that combination chemotherapy is the most effective treatment regimens based on just one drug [16][17][18]. This is because the different drugs act in slightly different ways, so together they increase their ability to kill cancer cells and by having a potentially greater impact induce the less severe side effects [15,17].…”
Section: Chemotherapy For Breast Cancermentioning
confidence: 99%